Drosophila carboxypeptidase D (SILVER) is a key enzyme in neuropeptide processing required to maintain locomotor activity levels and survival rate. (10th August 2019) - Pauls, Dennis; Hamarat, Yasin; Trufasu, Luisa; Schendzielorz, Tim M.; Gramlich, Gertrud; Kahnt, Jörg; Vanselow, Jens T.; Schlosser, Andreas; Wegener, Christian
Abstract: Neuropeptides are processed from larger preproproteins by a dedicated set of enzymes. The molecular and biochemical mechanisms underlying preproprotein processing and the functional importance of processing enzymes are well‐characterised in mammals, but little studied outside this group. In contrast to mammals, Drosophila melanogaster lacks a gene for carboxypeptidase E (CPE), a key enzyme for mammalian peptide processing. By combining peptidomics and neurogenetics, we addressed the role of carboxypeptidase D (dCPD) in global neuropeptide processing and selected peptide‐regulated behaviours in Drosophila . We found that a deficiency in dCPD results in C‐terminally extended peptides across the peptidome, suggesting that dCPD took over CPE function in the fruit fly. dCPD is widely expressed throughout the nervous system, including peptidergic neurons in the mushroom body and neuroendocrine cells expressing adipokinetic hormone. Conditional hypomorphic mutation in the dCPD‐encoding gene silver in the larva causes lethality, and leads to deficits in starvation‐induced hyperactivity and appetitive gustatory preference, as well as to reduced viability and activity levels in adults. A phylogenomic analysis suggests that loss of CPE is not common to insects, but only occurred in Hymenoptera and Diptera. Our results show that dCPD is a key enzyme for neuropeptide processing and peptide‐regulated behaviour in Drosophila . dCPD thus appears as a suitable target to genetically shut down total neuropeptide production in peptidergic neurons. The persistent occurrence of CPD in insect genomes may point to important further CPD functions beyond neuropeptide processing which cannot be fulfilled by CPE. Abstract : While the mouse uses carboxypeptidase E (CPE) over CPD in peptide processing, the Drosophila genome encodes only for a dCPD ( silver ) but not for a dCPE. Using peptidomics, we show that dCPD is indeed a key enzyme in neuropeptide processing. Mutating silver affects behaviour and survival. Surprisingly, a phylogenomic search revealed that most other insect genomes contain a gene for both CPD and CPE—similar to the vertebrate situation—while most Diptera and the Hymenoptera obviously have lost the CPE gene.